Prediction of shear strength of reinforced concrete squat shear walls-comparative studies - Rao, G. Appa; Sivaguru, V. (Journal of Structural Engineering, 2024)
The prediction of shear strength of RC walls by various empirical, semi-empirical and code equations is highly deviating. The accuracy of such predictions is a great concern for the designers. Such deviation in the prediction needs to be addressed. Several predicting equations proposed and reported prominently in various sources have been assessed through statistically based 333 selective experimental data points. The box and whisker plot has been developed for the scatter of the ratio of predicted-to-measured ultimate shear strength for all the predictive equations. The deviation of the predicted shear strength of RC walls as per the existing equations has been inferred. The prediction of the shear strength of RC shear wall by very few equations are in close proximity with the statistical experimental data. Though several factors influence the shear strength of RC walls, the role of vertical and horizontal reinforcement, axial load, and boundary elements is still debatable. The selective main factors influencing the shear strength of RC walls have been emphasised. The refined predictive model has been described from the assessment of the data in terms of influencing factors on the shear strength and behaviour of RC shear wall. The best predictions have been validated with the popularly accepted experimental results.